USE OF DIGITAL AND PSYCOREGULATORY TECHNOLOGIES IN THE PEDAGOGICAL AND PSYCHOLOGICAL TRAINING OF JUDGING STUDENTS - Kuniyazov, Kh. (SCIENCE and SOCIETY, 2026)
The article examines the effectiveness of using digital and psychoregulatory technologies in the pedagogical and psychological training of dzyudo students. The expediency of integrating digital educational tools, video analysis technologies, biological feedback, and psychoregulation into the training process is substantiated. During the pedagogical experiment conducted with students specializing in judo, the indicators of technical preparedness, psychological stability, and competitive reliability in the control and experimental groups were compared.
Keywords: judo; digital technologies; psychoregulation; pedagogical training; psychological resilience; students